The Development Process of Qinghai Mongolian Folk Songs Through Anthropological Perspectives - Han, Qin; Sensai, Peerapong (International Journal of Sociologies and Anthropologies Science Reviews, 2024)
Background and Aims: Qinghai Mongolian folk songs, cherished expressions of the Mongolian community's cultural identity, are the focal point of this anthropological study. The research aims to investigate the development process of Qinghai Mongolian folk songs through anthropological perspectives. Materials and Methods: Employed a comprehensive methodology integrating both ethnomusicology and anthropology on in-depth interviews with two key informants renowned for expertise. Additionally, participant observation techniques were applied, carriers of traditional knowledge, and agents fostering cultural continuity within the community. Results: This study resoundingly emphasizes the critical need to safeguard the exquisite tapestry of Qinghai Mongolian folk songs, serving as a melodious gateway into the soul of the Mongolian community. Beyond preservation, the study sparks curiosity for future exploration, beckoning researchers to unravel the regional intricacies, contemporary transformations, and dynamic community-driven conservation strategies that shape the ongoing narrative of these cultural treasures. Conclusion: This research contributes to the discourse on safeguarding traditional cultural expressions while celebrating the enduring beauty of Qinghai Mongolian folk songs and honoring the rich heritage of the Mongolian people in Qinghai.